South Korea's evolving Indo-Pacific strategy: Opportunities and challenges for cooperation with the EU - Eric J. Ballbach (Stiftung Wissenschaft und Politik (SWP), 2023)
South Korea has been late to embrace the concept of the Indo-Pacific. Its strategic approach developed from initial neglect to mere tactic acknowledgment and careful engagement under the Moon administration (2017-2022), to the now clear support for a distinct Indo-Pacific strategy under the Yoon administration (since 2022). While South Korea's Indo-Pacific strategy represents an important step in formulating its own interests in the region, its implementation will be influenced by the larger strategic environment, the dynamic relationships between a network of different actors in the region, and the coordination of its approach with like-minded partners. Despite the Yoon administration's closer alignment of its Indo-Pacific strategy with that of the US, there are ample opportunities to strengthen cooperation between the EU and the Republic of Korea (ROK or South Korea) on the Indo-Pacific. This is a consequence of overlapping interests regarding the Indo-Pacific region, which are expressed through strong similarities in the respective strategy papers of South Korea and the EU. Building on a solid existing basis of bilateral cooperation enabled by their strategic partnership, cooperation between the EU and the ROK should now be deepened beyond their already well-developed bilateral frameworks within the economic realm to the wider field of security cooperation. As South Korea's and the EU's Indo-Pacific strategies highlight similar areas of action, economic security, maritime security and cyber security are the most likely issue-areas in which the two sides will expand their links.
Keywords: 320; South Korea; North Korea; Strategy for a Free; Peaceful; and Prosperous Indo-Pacific Region (SFPPIP); Moon Jae-in; EU; USA; Russia; China; New Southern Policy (NSP); Free and Open Indo-Pacific (FOIP)